American identification a new approach to film scoring - Hubai Gergely (2012)
The immediate reception of the film music-themed concert during the 1950 International Music Congress in Florence as well as the debate around the event mark the first outspoken break between the American and European film music scene. The argument of the American and European delegates finally pointed out the obvious differences between the film music culture of the two continents in eloquent and explainable terms. These could be summarized in the following: 1) American film composers were specialized in a given field, while their European counterparts were interested in several different areas of music; 2) American film composers organized their work in a manufacture fashion, while the European composers were more self-reliant, and thus, looked down upon those who did not follow these methods; 3) these differences led to a legal dreadlock that made collaboration between European composers and American studios almost impossible. Traces of musical discrepancy may still be detected between the two continents’ usage of film music – this could perhaps explain some of the more subtle differences between American and European cinema.